Extent of the Factors Contributing to the Dropout Rate of Mindanao Children’s Library Foundation Incorporated (MCLFI) Scholars - Norai Mae Sumac; Emilou N Gallardo (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: The study seeks to determine the extent of the factors contributing to the dropout rate of scholars at the Mindanao Children’s Library Foundation Incorporated (MCLFI) in Barangay Manongol, Kidapawan City, during the second semester of the academic year 2023–2024. It specifically aims to examine the influence of family, personal, academic, peer, and environmental factors on dropout cases. Furthermore, it identifies the most common factor compelling MCLFI scholars to leave school and discontinue their educational pursuits. Methodology: A descriptive-quantitative design was employed to investigate the factors contributing to dropout. Fifty former MCLFI scholars were randomly selected as respondents. Data were gathered using a self-made survey questionnaire, validated by three research experts, covering family, personal, academic, peer, and environmental factors. Results were tabulated and analyzed using descriptive statistics to measure the extent of influence and determine the most prevalent reasons for scholar dropout. Main Findings: The results reveal that personal factors significantly influence scholar dropout, ranking highest among the categories measured. Issues such as lack of motivation, discipline, and self-related challenges hindered scholars from pursuing their education. On the other hand, environmental factors were identified as the least influential in shaping dropout decisions. Overall, the findings suggest that while external pressures matter, the internal struggles of learners exert greater influence on their persistence in completing academic requirements. Novelty/Originality of this study: This study is distinctive as it focuses on dropout cases within a foundation-based educational program, the MCLFI, a context rarely explored in dropout-related literature. Most research on academic attrition emphasizes public and private schools, while this study highlights the struggles of scholars supported by a non-governmental organization. By establishing that personal factors are more influential than family, peer, or environmental pressures, the research underscores the need for tailored interventions that address individual student challenges. It contributes to designing context-sensitive strategies that promote retention and reduce dropout among foundation-supported learners.